2003
DOI: 10.1002/esp.1002
|View full text |Cite
|
Sign up to set email alerts
|

Weathering and biokarst development on marine terraces, northwest Morocco

Abstract: Weathering features are described from an arid coastal area in northern Morocco which are indicative of invasive chasmolithic and endolithic microbial communities. Active weathering of marine terraces and karst development is associated with endolithic and epilithic algae responsible for boring, disintegration of matrix and mineral fabrics, solution and biomineralization that undermines the marine carbonate platform. Evidence of a range of biological weathering agents remains preserved, specifically calcified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The coastal terraces along Morocco's northern shores (north of Casablanca, Mohammedia to Rabat) are areas of considerable diagenetic activity indicated by the widespread occurrence of biominerals and phytokarst development (Duane 2001;Duane et al 2003). north to Rabat, are composed of Quaternary calcareous sandstones exhibiting cavernous, pitted, and honeycombed appearances especially along exposed headlands.…”
Section: Micro-geomorphology Of Pelagosite and Coniatolitementioning
confidence: 99%
See 2 more Smart Citations
“…The coastal terraces along Morocco's northern shores (north of Casablanca, Mohammedia to Rabat) are areas of considerable diagenetic activity indicated by the widespread occurrence of biominerals and phytokarst development (Duane 2001;Duane et al 2003). north to Rabat, are composed of Quaternary calcareous sandstones exhibiting cavernous, pitted, and honeycombed appearances especially along exposed headlands.…”
Section: Micro-geomorphology Of Pelagosite and Coniatolitementioning
confidence: 99%
“…The spray adds Ca to the surface of the terraces. The ultimate cause ofprecipitation ofpelagosite-coniatolite in and on sand surfaces was supersaturation of the trapped seawater laden with CO 2 from vadose waters entering the cliffs (Duane et al 2003). The loss of CO 2 by degassing is often the main driving force causing very high levels of supersaturation (Chafetz et al 1991) leading to the precipitation of calcium carbonate.…”
Section: Pm Detrital Grain (A) the Outer Surface Is Porous And Has Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Duane et al (2006) further suggested that a combination of biological weathering processes, abrasion, wave action, salt spray, and wetting/drying resulted in dissolution of the rocks, with the magnitude of platform deflation decreasing with distance from the platform edge. The interdependence of biologic communities to tolerable habitat conditions, in conjunction with spatial variations in the extent of physical and chemical weathering has led to the development of geomorphic gradients along low-lying coastal rocky exposures (Duane et al, 2003;Moses, 2003). In a study examining meso-and micro-karst morphologies within supratidal exposures of calcarenite on Lord Howe Island, Australia, Moses (2003) recognized three distinct geomorphic zones extending landward from the platform edge.…”
Section: Introductionmentioning
confidence: 99%
“…Coastal karst morphologies may vary as a function of geology, temporal and spatial locations, and the influences of physical, biological and chemical processes (Schneider and Torunski, 1983;Duane et al, 2003;Moses, 2003;Taborosi et al, 2004;De Waele et al, 2009). Physical and textural parameters such as composition, grain sorting, and packing play a significant role in determining the extent of dissolution or erosion.…”
Section: Introductionmentioning
confidence: 99%